2018
DOI: 10.1016/j.jpeds.2017.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Atherosclerosis in Pediatric Liver Transplant Recipients: Carotid and Aorta Intima-Media Thickness and Their Predictors

Abstract: Measures of long-term cardiovascular risk were associated with conditions that are more common in pediatric liver transplant recipients than nontransplanted peers, namely, diastolic hypertension and glucose intolerance. Larger, longitudinal studies are warranted to investigate whether cIMT could be useful for stratifying these patients' cardiovascular risk-and potential need for proactive intervention-during long-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
8
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 33 publications
4
8
2
Order By: Relevance
“…Elevated IMT, compatible with nascent atherosclerosis, was present in 57% of children in our cohort. This frequency is in line with the recently published study by Perito et al No exact prevalence of pathological IMT is reported in this study. However, graphic presentation of the study data suggests a prevalence of approximately 50%.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Elevated IMT, compatible with nascent atherosclerosis, was present in 57% of children in our cohort. This frequency is in line with the recently published study by Perito et al No exact prevalence of pathological IMT is reported in this study. However, graphic presentation of the study data suggests a prevalence of approximately 50%.…”
Section: Discussionsupporting
confidence: 94%
“…Although a relevant CV burden has been described in children after kidney transplantation (12,13) and, more recently, in children after hematopoietic stem cell transplantation, (14) data on the development of CV morbidity in pediatric LT recipients are still scarce. (15)(16)(17) Carotid intima-media thickness (IMT) and aortic pulse wave velocity (PWV) are established pediatric markers for subclinical CV target organ damage (TOD). (18) IMT reflects atherosclerosis, the development of atheromatous deposits in the arterial wall.…”
Section: Original Article | 753mentioning
confidence: 99%
See 2 more Smart Citations
“…Hyperglycemia and diabetes development in SOT is associated with a higher percentage of cardiovascular risk factors . In our study, diabetes‐specific data such as HbA1c and insulin dose were comparable between SOT and non‐SOT patients with diabetes.…”
Section: Discussionsupporting
confidence: 48%